Ghost times two - Hart, Carolyn G. (Hart, Carolyn G. Bailey Ruth ghost mysteries, 2016)
"Carolyn Hart--New York Times bestselling author of Ghost to the Rescue--returns with a new Bailey Ruth Ghost Novel in which one woman shatters the glass ceiling ... with a little help from beyond. Bailey Ruth Raeburn's latest mission is to guide the happy-go-lucky spirit of a deceased young man named Jimmy to the next life. But Jimmy is determined to watch over his still-living girlfriend Megan, whom he wants to be happy even without him--which is easier said than done. As if being haunted by her late boyfriend wasn't enough, Megan is dealing with an arrogant, manipulative senior partner who threatens to fire Megan's vulnerable secretary if Megan accepts a partnership at another law firm. She's in an impossible bind. Since Jimmy refuses to move on while Megan is being blackmailed, Bailey Ruth agrees to help him. But after the partner turns up dead and Megan is found at the crime scene, Bailey Ruth and Jimmy have to find a way to uncover a killer before the love of Jimmy's life is ordered to spend a lifetime behind bars.."--